Automatic Light Pipe Actuating System for Bimanual Robot-Assisted Retinal Surgery - He, Changyan (IEEE ASME Trans Mechatron, 2020)
Retinal surgery is a bimanual operation in which surgeons operate with an instrument in their dominant hand (more capable hand) and simultaneously hold a light pipe (illuminating pipe) with their non-dominant hand (less capable hand) to provide illumination inside the eye. Manually holding and adjusting the light pipe places an additional burden on the surgeon and increases the overall complexity of the procedure. To overcome these challenges, a robot-assisted automatic light pipe actuating system is proposed. A customized light pipe with force-sensing capability is mounted at the end effector of a follower robot and is actuated through a hybrid force-velocity controller to automatically illuminate the target area on the retinal surface by pivoting about the scleral port (incision on the sclera). Static following-accuracy evaluation and dynamic light tracking experiments are carried out. The results show that the proposed system can successfully illuminate the desired area with negligible offset (the average offset is 2.45 mm with standard deviation of 1.33 mm). The average scleral forces are also below a specified threshold (50 mN). The proposed system not only can allow for increased focus on dominant hand instrument control, but also could be extended to three-arm procedures (two surgical instruments held by surgeon plus a robot-holding light pipe) in retinal surgery, potentially improving surgical efficiency and outcome.